Right to work - Korpič - Horvat, Etelka (Anali PAZU HD, 2022)
The right to work is an important human right. The state must create possibilities for every individual to have the right to choose her/his profession, to work under healthy working conditions and to receive an adequate payment in order to attain a proper standard of living for herself/himself and her/his family.The Constitution of the Republic of Slovenia determines "the  freedom of work" instead of "the right to work" (Article 49 of the Constitution). The freedom of work contains the same elements as the right to work set out in the international legal acts, such as the right to choice of employment, the right to access each employment under equitable conditions and the prohibition of forced labour. Forced labour has been lately increasingly evident due to human trafficking, although international legal acts clearly stipulate that no one should be held in slavery or servitude or be required to perform forced or compulsory labour. In her paper, the author argues that voluntary work is a fundamental human right confirming the essence of a human being and human dignity.
Keywords: right to work; freedom of work; human right; forced labour; slavery